2007
DOI: 10.1007/s12031-007-0017-4
|View full text |Cite
|
Sign up to set email alerts
|

Opposing effects of proteasomes and lysosomes on LIFR: Modulation by TNF

Abstract: Urocortin, a potent peptide inhibitor of feeding behavior, can enter the brain from blood by leptin-facilitated permeation across the blood-brain barrier. Here, we show in cultured RBE4 cerebral microvessel endothelial cells that urocortin endocytosis is increased by leptin in a time- and dose-dependent manner. Fluorescently labeled urocortin (Alexa488-urocortin) shows vesicular trafficking localized in early endosomes at 1 min and the Golgi complex at 20 min. The endocytosis at 20 min was increased by 10 micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 37 publications
1
25
1
Order By: Relevance
“…This in vivo observation differs from our in vitro results in RBE4 cerebral microvessel endothelial cells, in which binding and endocytosis of LIF were reduced after TNF treatment accompanied by decreased LIFR and increased gp130 (40,41). Since the cell studies involved stimulation with TNF, rather than LPS, and a shorter duration of treatment than received by the mice, the discrepancy probably reflects the complexity of dynamic changes in vivo.…”
Section: Discussioncontrasting
confidence: 93%
“…This in vivo observation differs from our in vitro results in RBE4 cerebral microvessel endothelial cells, in which binding and endocytosis of LIF were reduced after TNF treatment accompanied by decreased LIFR and increased gp130 (40,41). Since the cell studies involved stimulation with TNF, rather than LPS, and a shorter duration of treatment than received by the mice, the discrepancy probably reflects the complexity of dynamic changes in vivo.…”
Section: Discussioncontrasting
confidence: 93%
“…At the level of the BBB, TNF not only modulates the functions of the constituent endothelial cells and their tight junctions but also exhibits its own receptor-mediated transport [25][26][27]. We have shown that TNF specifically modulates the expression and functions of the receptors for leukemia inhibitory factor in the cerebral microvessel endothelial cell line RBE4 [28,29]. How TNF regulates the functions of MDR1, a membrane protein encompassing 12-transmembrane domains [2,3], has not been fully characterized.…”
Section: Introductionmentioning
confidence: 99%
“…The reason for such dissociation of the direction of regulatory changes is not clear, but the involvement of NFκB transcription factor has been proved by use of specific inhibitors. TNF treatment causes a reduction of LIF-induced STAT3 activation and decreases LIF endocytosis by RBE4 cells [34,35]. The results suggest that LIFR (gp190) plays a greater role than gp130 in both LIF transport and signal transduction.…”
Section: Leukemia Inhibitory Factor (Lif) In Sci 4a Lif Transport Inmentioning
confidence: 88%
“…TNF treatment causes a dose-and time-dependent decrease of gp190 protein expression by post-transcriptional regulation, mainly at the level of protein degradation by ubiquitin-proteasome pathways [34]. Concurrently, there is an increase of gp130 mRNA and protein.…”
Section: Leukemia Inhibitory Factor (Lif) In Sci 4a Lif Transport Inmentioning
confidence: 99%